Redención de la pena privativa de libertad por trabajo y educación: beneficio penitenciario que refuerza la resocialización - Guadalupe Sánchez, Angela Sarilu (2021)
In the present investigation entitled "Redemption of the preventive sentence of freedom for work and education: prison benefit that reinforces resocialization", it aimed to analyze how the prison benefit of redemption of sentence for work and education reinforces the resocialization of the inmate, investigation of qualitative type, of a descriptive type that is supported by the theories of punishment, and where the nature of the Penitentiary Benefits as penological institutions constitute legal mechanisms tending to stimulate the readaptive attitudes of the inmates; whose regulation must be consistent with the integral function that our criminal system assigns to punishment, so it is up to the State to properly graduate them based on its criminal policy guidelines, making it imperative to establish a framework of intangible principles that, as a way of main beams limit the discretion of the political decision regarding them.